The use of antidementia therapy in non-dementia cognitive disorders associated with COVID-19 - Liubov, P.; Iashina, I. (European psychiatry, 2023)
IntroductionThe new coronavirus infection causes severe damage to the human body. One of the most serious complication is cognitive impairment.According to a meta-analysis by Maxime Taquet et al. (2021), which assessed neurological and psychiatric outcomes among 236,379 patients diagnosed with COVID-19, 1.7% of participants over 65 years of age were diagnosed with dementia.In a US online survey of 1,500 people (Sarah Ballou et al., 2020), about half reported difficulty concentrating on any task after experiencing COVID-19.It was also found that there is a decrease in the speed of reactions and problem-solving (Jeffrey D. Pyne et al., 2021).There are a number of studies that present the evidence-based efficacy of acetylcholinesterase (AChE) inhibitors in dementia prevention.However, in accordance with clinical guidelines for cognitive disorders in the elderly, anti-dementia drugs are not used at the stage of mild to moderate cognitive impairment (Ministry of Health of the Russian Federation, 2020).ObjectivesThe use of AChE inhibitors in cognitive impairments that do not reach the degree of dementia.MethodsResearch data from open sources.ResultsThe development of early cholinergic deficiency correlates with the development of cognitive impairment, while acetylcholine has a pronounced neuroplastic effect and increases the number of neurons (Gabriela Dumitrita Stanciu et al., 2019).In a double-blind, placebo-controlled study, a positive effect of rivastigmine was found in patients with mild to moderate cognitive impairment. The study’s results show that rivastigmine treatment (3, 6, 9 mg/day) for six months increases brain activity of the hippocampus in the control group by 32,5%. Rivastigmine prevented the clinical progression of symptoms of cognitive impairment and caused activation of some parts of the cerebral cortex (Nagaendran Kandiah et al., 2017).In a study by Wolfson C. et al. (2002), it was found that rivastigmine can slow down the development of cognitive impairment for at least six months in patients with mild to moderate massive cognitive dysfunction. Subjects treated with 1 to 21 mg per day for 7 to 12 weeks got more favorable ADAS-cog scores for the six months after treatment. While those who took the drug in doses of 6 to 12 mg showed a more pronounced positive effect compared to the placebo group.The Luca Rozzini in 2006 conducted a study based on 59 subjects with mild cognitive impairment. 15 subjects received both neuropsychological examination and acetylcholinesterase inhibitors. As a result, the remaining subjects were behind in terms of abstract thinking and behavioral symptoms, in comparison with a combined treatment group.ConclusionsIt is advisable to conduct further studies on the effectiveness of AChE inhibitors to prevent the progression of mild to moderate cognitive impairment and their transition to dementia.Disclosure of InterestNone Declared